The concordance of self-reported and officially recorded criminal onset: results from a sample of Australian prisoners$jJason L. Payne, Alex R. Piquero - Payne, Jason (Crime & delinquency, 2018)
This study examines the concordance of self-reported and officially recorded criminal onset among a sample of prisoners in Queensland, Australia. Classified into one of four developmental stages, Gwet’s Agreement Coefficient 1 (AC1) is used to examine the concordance of these two popular data sources. Analysis is conducted across seven offense types, and comparisons are made between Indigenous and non-Indigenous offenders. Results indicate moderate agreement between self-reports and official records with greater concordance for violent and serious property offenses. With few exceptions, self-reported onset precedes officially recorded onset, and concordance was greater for Indigenous offenders. These findings have important methodological implications for criminological research, in particular, developmental and life-course theory, which emphasizes the theoretical importance of the timing and sequencing of criminal events.